2013
DOI: 10.1007/s13197-013-0941-y
|View full text |Cite
|
Sign up to set email alerts
|

Hot air drying characteristics of mango ginger: Prediction of drying kinetics by mathematical modeling and artificial neural network

Abstract: Mango ginger (Curcuma amada) was dried in a through-flow dryer system at different temperatures (40-70°C) and air velocities (0.84 -2.25 m/s) to determine the effect of drying on drying rate and effective diffusivity. As the temperature and air velocity increased, drying time significantly decreased. Among the ten different thin layer drying models considered to determine the kinetic drying parameters, semi empirical Midilli et al., model gave the best fit for all drying conditions. Effective moisture diffusiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
24
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(36 citation statements)
references
References 51 publications
8
24
0
2
Order By: Relevance
“…Thus, the Midilli et al and Two Term models were found to be best models to represent the thin-layer drying characteristics of the date slices. These observations are in good agreement with earlier results reported for the Midilli et al model in describing the thin-layer drying of pear (Doymaz, 2013) and mango ginger (Murthy & Manohar, 2014) and for the Two term model in drying of sultana grapes (Yaldiz et al, 2001) and squash seeds (Chayjan et al, 2013).…”
Section: Fitting Of Drying Curvessupporting
confidence: 92%
“…Thus, the Midilli et al and Two Term models were found to be best models to represent the thin-layer drying characteristics of the date slices. These observations are in good agreement with earlier results reported for the Midilli et al model in describing the thin-layer drying of pear (Doymaz, 2013) and mango ginger (Murthy & Manohar, 2014) and for the Two term model in drying of sultana grapes (Yaldiz et al, 2001) and squash seeds (Chayjan et al, 2013).…”
Section: Fitting Of Drying Curvessupporting
confidence: 92%
“…It is also rich major components including starch, phenolic acids, volatile oils, curcuminoids and terpenoids like difurocumenonol, amadannulen and amadaldehyde (Policegoudra et al 2011). Many aspects of processing like drying (Krishna Murthy and Manohar 2013a), grinding (Krishna Murthy and Manohar 2013b) and extraction (Krishna Murthy and Manohar 2014) of mango ginger have been studied by the authors. Extraction of mango ginger for its bioactives on a commercial scale is not in practice and such extraction shall result in value-added products.…”
Section: Introductionmentioning
confidence: 99%
“…The ANN can establish a functional relationship between input and output variables by training and learning (Chojaczyk, Teixeira, Neves, Cardoso, & Guedes Soares, ). In recent years, ANN models have been studied for the modeling of drying of potato cubes (Azadbakht, Aghili, Ziaratban, & Torshizi, ), bay leaves (Aktaş, Şevik, Özdemir, & Gönen, ), mango ginger (Murthy & Manohar, ), sour cherry (Motavali, Najafi, Abbasi, Minaei, & Ghaderi, ), onion (Jafari, Ganje, Dehnad, & Ghanbari, ), kiwi (Mahjoorian et al, ), zucchini (Tavakolipour, Mokhtarian, & Kalbasi‐Ashtari, ), green bell pepper (Jafari, Ghanbari, Ganje, & Dehnad, ), and turnip slices (Kaveh & Chayjan, ). But, there is no study about comparison between ANN model and mathematical models for PVOD treated and non‐pretreated figs during drying.…”
Section: Introductionmentioning
confidence: 99%